Study of Effective Communication Patterns in personnel of Tehran 15 Khordad Hospital - Saeed HEDAYATI LAMOUKI; Maliheh KHAKVATI; Hanieh JAFARIAN; Zahra HASANI; Masoome BABAEI (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Relationships and how it is oriented towards organizational goals is one of the important issues for hospital managers. The purpose of the present study was to identify the patterns of communication between the staff of the 15 Khordad Hospital in Tehran. Methods: This study was a descriptive study. Using the Cochran formula, a sample population of 194 people was estimated that 98 nurses, 46 administrative staff, 27 service personnel and 23 physicians were selected by simple random sampling. The data collection tool was a demographic checklist and Robbins' Organizational Communication Inventory (1998). Data were analyzed using SPSS software version 22, one-way ANOVA and Tukey test. Results: 61.3% of the participants in the study reported their communication moderate and of 38/7 % the participants reported strong communication. One-way analysis of variance (ANOVA) showed that at the significance level of 0.05, the difference in mean score of organizational communication between different administrative, service, nursing and medical groups is significant. Discussion: Each occupational category uses a different communication pattern based on its situation in the hospital and the level of interaction with other occupational categories and more employment in the treatment area. It seems that the proportional distribution of facilities and powers in the hospital can affect the improvement of the communication model.